Compressive Strength of Disperse Reinforced Concrete with Basaltic Fiber (Texas Journal of Engineering and Technology, 2022)
The article describes the results of studies on the compressive strength of the distribution of reinforced concrete with basalt fibers and the optimal amount of basalt fiber and fiber length. For the experiments, 26 series of concrete cubic samples with sides of 100x100x100 mm were prepared by the standard requirements. Particular attention was paid to the process of the standard of preparation requirements and vibration of samples during the placement of concrete mixes in the molds. The prepared samples were removed from the molds after standing in the room for 1 day and the samples were marked and stored in a normal solidifying chamber for 7 days and 28 days. Basalt fibers of 5, 10, 15, 20, 30 mm lengths were added to the concrete. The obtained scientific results show that the compressive strength of concrete with the addition of basalt fibers increases by 15-20% compared to ordinary concrete.